Fluidized-bed combustion of coal - Naude, Donald Peter (Department of Mechanical Engineering, 2024)
A general review of the literature pertaining to the combustion of coal in an atmospheric fluidized bed of ,inert particles is presented. In particular, the ~henomena of fluidization and combustion have been investigated and the status of research and development in various parts of the world is considered. A 300 mm diameter refractory lined open top atmospheric fluidized bed combustor has been built to study the combustion efficiencies and entrainment rates of the fluidized-bed combustion process in shallow fluidized beds, with static bed heights ranging from about 150 mm to 2JJ mm. A low pre5sure drop type of distriLutor WES used for all of the tests so as to test a system compatible with most industrial requirements. As the combustor vessel is refractory lined, cool1ng is provided by supplying air to the rig well in excess of that required for stoichiometric combustion. As a result, no oxygen deficient regions occur within the fluidized bed, ensuring complete combustion of both the fixed carbon component of the coal to carbon dioxide and the volatile component within the bed section. Experimental results have been obtained from the combustion of a coal with a high fines content of which there is at present a supply which exceeds the demand. The coal has been burned in an inert bed comprising a closely graded silica sand. It has been found possible to correlate the combustion efficiencies in terms of the bed temperature, superficial gas velocity and the static bed height within the following ranges of these parameters: Bed Temperature Gas Ve~ocity Static Bed Height 700 to 1000°c 0,9 to 1,5 m/s 150 to 230 mm By using a bed material substantially different from the coal feed, it has been found possible to separate the (ii) entrainment rate into two components, the first due to elutriation and the second as a result of splashing. However only qualitative conclusions have been drawn from the splashing phenomenon. The incieased ~plashing rates associated with the deeper beds may be attributed in ~art to the possible transition from a bubbling to~ slugging flow regime taking place in the fluidized bed. A semi-quantitative model has been derived based on the work of a few authors to describe the combustion and entrainment phenomena. Although the model predicts trends satisfactorily, much work is required to determine attrition rate constants and the nature of the resulting ash on combustion of the coal particle as these parameters are artificially supplied as input to the computer model.